Analisis Tingkat Kepuasan Konsumen pada Konter Abian Cell Store di Kabupaten Batang Hari ditinjau dari Kualitas Pelayanan dan Kelengkapan Produk - Ahmad Fithoni; Akhmadi Akhmadi; Andi Pratama (CITRA EKONOMI, 2022)
The purpose of the study was to analyze the level of consumer satisfaction at the Abian Cell Store counter in Batang Hari Regency in terms of Service Quality and Product Completeness. The research was conducted quantitatively with the number of respondents as many as 30 people by looking at the highest to lowest order of respondents' satisfaction levels on the quality of service and completeness of the products provided by the Abian Cell Counter, followed by looking at the satisfaction levels of respondents based on gender, age and education.The results showed that the level of consumer satisfaction with the Abian Cell Store counter seen from the services provided to consumers was in the Satisfied category with an index value of 3.99. Meanwhile, based on the highest level with an index value of 4.23, it is satisfied because the counter employees are alert and fast in providing services and the counter sells many brands of the products provided. Meanwhile, the lowest level of satisfaction with an index value of 3.63 is due to the attention and actions of employees towards consumer complaints. Judging from gender, it is known that those who have the highest and lowest levels of satisfaction are female consumers, seen from the age of those who have the highest level of satisfaction at the age of 21-25 years while the lowest is at the age of less than 20 years. Judging from the level of education, the highest and lowest levels of consumer satisfaction are consumers who have an equivalent high school education.